Mobility of Muslim students seeking higher education: A dream fraught with challenges (Comparative & International Education Series, 2021)
The current socio-political conditions of the world have led to a tension between university's commitment to religious equality and its religion profiling strategies. The vetting and surveillance of Muslim students is preventing many students from gaining access to higher education globally, thus thwarting student's mobility. This chapter will talk about Muslim students in particular from Central Asia and the Middle East who would want to travel to UK, USA and Australia seeking higher education. Qualitative interviews will be conducted with students from Iraq, Turkey and parts of Central Asia. The chapter aims to highlight some of the current issues faced by Muslim students and students seeking alternative arrangements.